2018
DOI: 10.3389/fpsyt.2018.00456
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Habenula Volume in Schizophrenia and Bipolar Disorder

Abstract: The habenula (Hb), a bilateral nucleus located next to the dorsomedial thalamus, is of particular relevance to psychiatric disorders based on preclinical evidence linking the Hb to depressive and amotivational states. However, studies in clinical samples are scant because segmentation of the Hb in neuroimaging data is challenging due to its small size and low contrast from the surrounding tissues. Negative affective states dominate the clinical course of schizophrenia and bipolar disorder and represent a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“…For example, DBS of LHb in rats reduced sucrose seeking and cocaine seeking behavior (51, 52) consistent with the putative role of Hb in addiction (17,34,53,54). Furthermore, studies have demonstrated that the Hb plays a role in the pathophysiology of a number of neuropsychiatric disorders beyond depression and addiction such as schizophrenia (15,55,56), bipolar disorder (BD) (15,33,(57)(58)(59), obsessive-compulsive disorder (OCD) (60,61) and autism (62).…”
Section: Introductionmentioning
confidence: 75%
“…For example, DBS of LHb in rats reduced sucrose seeking and cocaine seeking behavior (51, 52) consistent with the putative role of Hb in addiction (17,34,53,54). Furthermore, studies have demonstrated that the Hb plays a role in the pathophysiology of a number of neuropsychiatric disorders beyond depression and addiction such as schizophrenia (15,55,56), bipolar disorder (BD) (15,33,(57)(58)(59), obsessive-compulsive disorder (OCD) (60,61) and autism (62).…”
Section: Introductionmentioning
confidence: 75%
“…2018 ; Drobisz and Damborská 2019 ), schizophrenia ( Zhang et al. 2017 ; Schafer et al. 2018 ), and panic disorders ( Pobbe and Zangrossi 2008 ; Mathuru and Jesuthasan 2013 ; Mathis and Kenny 2018 ; Ma et al.…”
Section: Diversity Of Cell Types In the Brain And Applications Of Sinmentioning
confidence: 99%
“…In addition to ADHD and MDD, habenular deficits have been implicated in other psychiatric disorders. As is the case with MDD, although a relatively large number of animal model studies have provided support for habenular deficits in schizophrenia ( Lecourtier and Kelly, 2005 ; Heldt and Ressler, 2006 ; Lecourtier et al, 2006 ; Boulos et al, 2017 ; Fakhoury, 2017 ; Li et al, 2019 ; Hu et al, 2020 ) and drug addiction ( Velasquez et al, 2014 ; Boulos et al, 2017 ; Fakhoury, 2017 ; Mathuru, 2018 ; Mathis and Kenny, 2019 ; Hu et al, 2020 ), there has been little or inconsistent evidence regarding habenular deficits in human patients with these disorders ( Shepard et al, 2006 ; Ranft et al, 2010 ; Boulos et al, 2017 ; Fakhoury, 2017 ; Zhang et al, 2017 ; Schafer et al, 2018 ; Germann et al, 2020 ; Hu et al, 2020 ).…”
Section: Habenula As a Neuronal P-factor?mentioning
confidence: 99%